A Predominant Oxidative Renal Metabolite of Empagliflozin in Male Mice Is Cytotoxic in Mouse Renal Tubular Cells but not Genotoxic. (November 2017) - Smith, James D.; Huang, Zimei; Escobar, Patricia A.; Foppiano, Pamela; Maw, Hlaing; Loging, William; Yu, Hongbin; Phillips, Jonathan A.; Taub, Mitchell; Ku, Warren W.
In a previously reported CD-1 mouse 2-year carcinogenicity study with the sodium glucose cotransporter-2 inhibitor empagliflozin, an increased incidence of renal tubular adenomas and carcinomas was identified only in the male high-dose group. Follow-up investigative studies have shown that the renal tumors in male high-dose mice were preceded by a number of renal degenerative/regenerative findings. Prior cross-species in vitro metabolism studies using microsomes identified an oxidative metabolite (M466/2) predominantly formed in the male mouse kidney and which spontaneously degrades to a metabolite (M380/1) and reactive 4-OH crotonaldehyde (CTA). In order to further evaluate potential modes of action for empagliflozin-associated male mouse renal tumors, we report here a series of in vitro investigative toxicology studies conducted to evaluate the cytotoxic and genotoxic potential of empagliflozin and M466/2. To assess the cytotoxic potential of empagliflozin and M466/2, a primary mouse renal tubular epithelial (mRTE) cell model was used. In mRTE cells, M466/2-derived in vitro 4-OH CTA exposure was cytotoxic, while empagliflozin was not cytotoxic or mitogenic. Empagliflozin and M466/2 were not genotoxic, supporting an indirect mode of action for empagliflozin-associated male mouse renal tumorigenesis. In conclusion, these in vitro data show that M466/2-derived 4-OH CTA exposure is associated with cytotoxicity in renal tubule cells and may be involved in promoting compound-related in vivo renal metabolic stress and chronic low-level renal injury, in turn supporting a nongenotoxic mode of tumor pathogenesis specific to the male mouse.